Efektivitas Aplikasi Program Pendataan Kesejahteraan Sosial Next Generation Di Kabupaten Gowa - Husri, Husri; Usman, Djailan; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine the effectiveness of the application of the Next Generation social welfare data collection program in Gowa Regency. This study used a qualitative method. The number of informants in this study was 5 people. Field research in the form of observation, in-depth interviews and document research. The results of this study showed that the effectiveness of the application of the next generation social welfare data collection program in Gowa Regency had been running as it should be seen from the perspective of the accuracy of the target programs of the poor and neglected children related to the application of the social welfare data collection program that had been running and up to now, the socialization aspect of the social service program had conducted a socialization program for collecting data on the social welfar, to achieve the application of the social service program, made commitments with village and sub-district government officials with the assistance of the village community empowerment service so that the data collection process through the SIKS-NG application run in the village and sub-district. Furthermore, for monitoring after the program carried out by the social service was quite effective by monitoring the poor and neglected children who had been data and given assistance after they were empowered provided by the government properly and correctly. Keywords: Application, Next Generation Social Welfare Data Collection Program